Animal Magnetism; A Mesmerizing Yet Controversial Past of Healing Sciences - Noushad , Shamoon (International Journal of Endorsing Health Science Research, 2020)
Background: Animal magnetism gained popularity in the 18th century specifically among Europeans and the people from the United States. The Mesmer’s theory on animal magnetism emphasized the presence of invisible natural force in all living organisms i.e. these natural forces exists as magnetic fluid whose abnormal flow was somehow linked to all diseased conditions. Methodology: The article tracks the history and the modern concept of animal magnetism. The literature was searched using the terms Mesmerism, Animal Magnetism, Healing, and French trials, etc. via Google Scholar, PubMed, Research Gate, and Scopus. Results: Mesmer drew the idea in line with scientific advances involving forces; gravity, electricity, and magnetism, etc. Although the magnetic fluid component presumed by his theory didn’t work out so well. But his theory marked the beginnings of some very factual and clinically beneficial aspects like hypnosis and healing outcomes. Conclusion: In conclusion, the popular report which was chaired by Franklin, was the main deliberate investigation of what we currently know as hypnosis. While modern-day hypnosis has earned the approval because its effects have been statistically proven in several controlled trials.